Developing “Leadership Intelligence (CI2) Framework” Inside Social Media to Develop An Ethical Leader using the Johari Window Method - Indra Gamayanto; Henry Christian; Sasono Wibowo; De Rosal Ignatius Moses Setiadi; Devi Purnamasari; Titien S sukamto (Indonesian Journal of Information Systems, 2019)
At this time, leadership and social media are two things that cannot be separated. Social media becomes an information technology media for leaders to be able to communicate about their vision and purpose. Therefore, leaders must be able to use social media effectively in order to influence the community with what they think. There are three problems caused by leaders in social media which are classified into three types such as narcissistic, compulsive and paranoid. These three things become big problems in leadership on social media and therefore, we need the formula to solve the problems. The Johari Window method is a method that has four perspectives in developing four leadership classifications such as open leaders, blind leaders, hidden leadership, and unknown leaders. If these three types and four classifications are put together, a framework will be produced called "Leadership Intelligence (CI2) Framework", the next one will produce a formula S = W.L2, where this formula will produce wise leaders on social media. This journal is the development of the journal Developing "Framework Intelligence (CI3)" Inside Social Media Using Johari Window Methods and The Development and Implementation of Wise Netizen (E-Comment) In Indonesia. As a result, this journal will give an answer and solve the problem of an ethical leader on social media and how to decrease a hoax that can affect the leader on social media. This research will continue until it produces a CI1 formula that will combine culture and leadership into a social media formula in generating positive communication, creating a positive culture and making a big impact on society.